MUI Dan Dinamika Sosial Politik (Studi Munculnya Fatwa Hukum Golput) - Yusefri Yusefri (Al-Azhar Islamic Law Review, 2022)
Fatwa is recognized as having a very urgent role, because it is an instrument in responding to various legal issues that are asked by parties that require legal clarity. Because of this, fatwas will always be needed from time to time. In the context of the implementation of the democratic party, the Indonesian Ulama Council (MUI) issued a fatwa  on law forbidden (haram) for those who do not want to use their voting rights or are called the white group (Golput) during the general election (Election). This fatwa turned out to be pro and contra in the community. This article focuses on its study by raising the issue of how the construction of the socio-political dynamic conditions underlies the birth of the MUI fatwa. The analysis of the study of this article uses a qualitative descriptive method. Based on the data and analysis, the results of this study indicate that the emergence of the Haram Golput fatwa was motivated by the phenomenon of decreasing community participation (the people) giving their voting rights in elections and full of political interests of certain parties, so it can be seen that the socio-political dynamics at that time influenced the emergence of the MUI fatwa on law forbidden